2014
DOI: 10.1111/acel.12300
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane enhances progerin clearance in Hutchinson–Gilford progeria fibroblasts

Abstract: Hutchinson–Gilford progeria syndrome (HGPS, OMIM 176670) is a rare multisystem childhood premature aging disorder linked to mutations in the LMNA gene. The most common HGPS mutation is found at position G608G within exon 11 of the LMNA gene. This mutation results in the deletion of 50 amino acids at the carboxyl-terminal tail of prelamin A, and the truncated protein is called progerin. Progerin only undergoes a subset of the normal post-translational modifications and remains permanently farnesylated. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 45 publications
16
95
0
Order By: Relevance
“…Additionally, in mock-treated cultures, most HGPS nuclei exhibited increased progerin accumulation at the nuclear envelope, with aggregates in certain areas as revealed when stained with anti-progerin antibodies (Fig 2D, upper panels). The HGPS nuclei that appeared normal showed reduced progerin staining [20]. Overall, both the number of bright progerin-positive nuclei and the signal intensity of these nuclei were reduced in temsirolimus-treated HGPS cells compared with mock-treated HGPS cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in mock-treated cultures, most HGPS nuclei exhibited increased progerin accumulation at the nuclear envelope, with aggregates in certain areas as revealed when stained with anti-progerin antibodies (Fig 2D, upper panels). The HGPS nuclei that appeared normal showed reduced progerin staining [20]. Overall, both the number of bright progerin-positive nuclei and the signal intensity of these nuclei were reduced in temsirolimus-treated HGPS cells compared with mock-treated HGPS cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mock-treated HGPS fibroblasts exhibited a significant increase in basal ROS levels (16.6%, p = 0.003) compared with normal cells (Fig 4G) [20]. Temsirolimus treatment of normal and HGPS cells resulted in no significant changes in ROS levels (Fig 4G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, p32 silencing significantly impaired both starvation-and rapamycin-induced autophagic flux [166]. Because AMPK has also been shown to regulate autophagy by phosphorylating and activating ULK1 and both rapamycin (mTOR inhibitor) and sulforaphane (isothiocyanate found in cruciferous vegetables) have each been shown to enhance autophagic clearance of progerin, a novel AMPK-p32 axis is further implicated, potentially decreasing progerin production via alternative splicing modulation while enhancing progerin clearance through autophagic induction [32,167,168]. Strikingly, Rivera-Torres et al showed that fibroblasts from HGPS patients exhibited a severe impairment in mitochondrial oxidative phosphorylation, characterized by markedly lower than normal expression of the mitochondria respiratory chain components cytochrome c, the complex V protein b-ATPase, and the complex IV component cytochrome c oxidase subunit I (COXI) compared to control fibroblasts [169].…”
Section: Ampk Activation and Mitochondrial Atp Production Is Essentiamentioning
confidence: 99%